Collection and Diversity: in search of new collections management methodologies (Cadernos de Sociomuseologia, 2021)
This article presents the theoretical-methodological aspects of the museum collections management processes from the perspective of cultural and sexual diversity, aiming at a LGBT collections policy. The general objective is to reflect on the conception of new methodologies for a LGBT collections management policy at the Museum of Sexual Diversity. The approached methodology reflects the 4 phases of the extension project Collection and Diversity: mapping and collection policy in museums, in order to systematize the action steps that involve the identification, contextualization, action and evaluation of the research process and safeguard of the collection. We consider that the elaboration of a normative document must necessarily reflect principles, values ​​and the identity of the institution, so that certain methodological choices are essentially political. In short, we identified the need to build instruments and procedures in the management of collections and museum documentation that meet diversity, so that they are respected and valued.Keywords: Collection management. LGBT museology. Museum of Sexual Diversity. Collections management policy. Museum documentation.